ENHANCING MOTIVATION OF THE EFL LEARNERS BY INTEGRATING TECHNOLOGY - Tahmina, Tania (Universitas Islam Sumatera Utara (UISU), 2022)
Motivation plays an important role in EFL learning. For the twenty-first century technology-savvy learners, teachers can resort to advanced technology to enhance and sustain their motivation. The present study explores the motivational orientations of the undergraduate EFL learners of Jagannath University, Dhaka, Bangladesh and the teacher’s awareness to equip their learners with appropriate technological knowledge to ignite their motivation for learning English effectively. There were two research questions in this study. The first question was whether the learners were integratively or instrumentally motivated. The second question dealt with the contribution of technology-enhanced language pedagogy to assist the learners’ motivational orientations in the blended classrooms. To find out the first research question, a paired samples t-test was conducted. The findings revealed that students’ integrative motivation was noticeably higher than instrumental motivation. A semi-structured interview of the language teacher was taken to answer the second question. The findings revealed that the learners were integratively motivated and the language teacher arranged technologically equipped classroom in order that the students would feel an inner urge to learn the language enthusiastically.